Ethnic composition of Moldavia (Moldova) and Wallachia (Voloshchyzna) in the Middle Ages - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the multiethnic character of Moldavia and Wallachia from the Middle Ages until the beginning of the eighteenth century. The author’s aim is to present the settlement and migration processes that shaped the ethnic structure of both Romanian principalities. The study applies a historical-demographic method based on narrative and documentary sources. The findings show that for centuries the region served as a meeting place for numerous ethnic groups, including Dacians, Slavs, Hungarians, Pechenegs, Cumans, Tatars, Germans, Roma, and Vlach populations. Particular importance is attributed to Vlach migrations, which in the thirteenth and fourteenth centuries led to the emergence of independent political entities. The author also emphasizes the role of German colonization, Ruthenian influences, and the presence of steppe peoples. The conclusions indicate that Moldavia and Wallachia were areas of long-term coexistence among many ethnic groups, which had a fundamental impact on the development of their culture and statehood.